2016
DOI: 10.1016/j.rtbm.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Good practices for advancing urban mobility innovation: A case study of one-way carsharing

Abstract: Transforming urban mobility requires integrating public with private services into a single transportation system. Local governments and private companies face the challenge of how to coordinate themselves. An emblematic example is one-way carsharing (shared use of a fleet of vehicles that are typically free-floating throughout an urban area). Surprisingly, good practices for public and private players driving this change remain relatively undocumented. This paper proposes a systematic and balanced public-priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
(61 reference statements)
0
18
0
5
Order By: Relevance
“…Some other cities also introduced CS demonstration and treated it as a sustainable business service, such as the Autolib programme in Paris, and the RFP (request for proposals) programme in San Francisco, which focused on reserving on-street parking spaces for CS vehicles. Munich allows free-floating carsharing operators to park everywhere and has lowered the price of the parking permit to €900 instead of €1800 for free-floating cars [83,84]. Many studies have argued that the success of the ECS service comes from close partnership between governments and ECS companies [85].…”
Section: Discussionmentioning
confidence: 99%
“…Some other cities also introduced CS demonstration and treated it as a sustainable business service, such as the Autolib programme in Paris, and the RFP (request for proposals) programme in San Francisco, which focused on reserving on-street parking spaces for CS vehicles. Munich allows free-floating carsharing operators to park everywhere and has lowered the price of the parking permit to €900 instead of €1800 for free-floating cars [83,84]. Many studies have argued that the success of the ECS service comes from close partnership between governments and ECS companies [85].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in the face of the emergence of car-sharing with positive influences, whether people’s preferences for travel modes will change and the factors influencing people’s choice of car-sharing travel are also very extensive [ 18 , 19 ]. In addition, the widespread use by people and the continuous emergence of car-sharing enterprises have given rise to a series of studies on operation management and vehicle scheduling [ 20 , 21 ]. Therefore, scholars at home and abroad mainly study car-sharing from three aspects: its development advantages, influencing factors that lead people to use car-sharing, and the operation and management of the car-sharing market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study found that the economic performance of urban car-sharing systems depends on fleet size, station or free-parking-area location decisions, pricing policies, etc., and this finding may be used by the government to strictly estimate the impact on car-sharing usage, and also enable operators to better manage their operating systems [ 40 ]. At the same time, in terms of market management, Terrien et al [ 21 ] emphasized the importance of cooperation between the public and private sectors. They argued that both the government and car-sharing companies should have specific management departments which are independent of the car-sharing operations and carry out management innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research field of car sharing, especially free-floating car sharing, is mostly investigated in German field studies on car2go fleets (Schmöller, Weikl, Müller, & Bogenberger, 2015) and on a few international test fields (Wielinski, Trépanier, & Morency, 2015;Terriena, Maniak, Chenb, & Shaheen, 2016;Ciari, Balac, & Balmer, 2015). This research field is enhanced by focusing on electric vehicles in free-floating car sharing (Firnkorn & Müller, 2015).…”
Section: Digital Transformation In the Automotive Sectormentioning
confidence: 99%